Penerapan model pembelajaran SAVI (somantic, auditory, visualization, intellectually) terhadap kemampuan representasi matematis siswa - Ayu Siti Nurhamidah; Zuli Nuraeni; Uba Umbara (Program Studi Pendidikan Matematika STKIP Muhammadiyah Kuningan, 2018)
This study aims to examine in depth about the ability of students 'mathematical representation and its improvement using the Somantic, Auditory, Visualization, Intellectually (SAVI) learning model, and to determine students' responses to SAVI learning. This study involved the experimental class and the control class taken from class VII (Seven) MTs Mishbahul Huda Kalimanggis District 2017/2018 Academic Year. The study used a descriptive test instrument to evaluate the students' mathematical representation skills and to use students' response questionnaires to find out students' responses to the applied learning. From the results of the pretest it was found that the mean score of the ability of the mathematical representation of the control class was 15.69 while the experimental class was 14.70. Through the t test on this value it is known that the value of t count = 1.41. While the degrees of freedom of 5% and dk = 44 are known to be t table = 2.732. From these two data we know that - 2.732 <1.41 <2.732 then fulfills H0 acceptance criteria which means that both classes have the same initial representation ability. Meanwhile from the post-test results it is known that the mean representation score of the control class is 26.91 and the average score of the mathematical representation of the experimental class is 33.33. From the results of the t test on this value obtained tcount = 3.21 and t table = 2.732. From the two data, it is known that -2,732 <3,21 <2,732, then tcount is not found in the reception area H0. This means that after treatment the ability of the experimental class mathematical representation is better than the control class. From the results of the z test the N-Gain score obtained zcount = -3 and ztable = 1.71. From the two data, it is known that -3 <1.71 then thitung is in the reception area H0. This means that after the treatment increases the mathematical representation ability of the experimental class is not in the high category. In addition, from the results of the student response questionnaire, it was found that students showed a positive response to the SAVI learning model.